Cation Substitution Induced Adjustment on Lattice Structure and Photoluminescence Properties of Mg14Ge5O24:Mn4+: Optimized Emission for w‐LED and Thermometry Applications. Issue 12 (16th April 2019) - Liang, Sisi; Li, Guogang; Dang, Peipei; Wei, Yi; Lian, Hongzhou; Lin, Jun
Abstract: Currently, Mn 4+ ‐activated red‐emitting materials are the research hotspot due to their promising application in phosphor‐converted white light‐emitting diodes (w‐LEDs). Here, a typical cation substitution strategy is reported to optimize Mn 4+ ‐doped germinate phosphor for improving luminescence performances. The effect of cation substitution for Ge 4+ ions by Ti 4+, Sn 4+, and Si 4+ ions on lattice structure, photoluminescence properties, and thermal stability of the as‐prepared Mn 4+ ‐doped germinates is systematically investigated. A significant improvement of emission intensity with Ti 4+ doping should benefit from the resonance emission enhancement effect. Some lattice distortion defects contribute to the thermal stability enhancement, which plays a role in driving the excited phonon traps to compensate the energy loss of nonradiative transition. Surprisingly, abnormal variation in intensity of anti‐Stokes and Stokes emission peaks with changing temperature is first observed, revealing a potential application in thermometry. The electroluminescence performances of as‐fabricated w‐LED devices using Mg14 Ge5 Ti0.5 O24 :Mn 4+ red phosphor are evaluated, which possess higher color rendering index ( R a = 87.3) and luminous efficiency (109.42 lm W −1 ) as well as lower color correlated temperature (3566 K) than those using Cs2 GeF6 :Mn 4+ and CaAlSiN3 :Eu 2+ red phosphors. The results reflect the superiority of the studied phosphor in w‐LEDs and optical thermometry areas. Abstract : Based on cation substitution in Mn 4+ ‐doped germanate, the luminescence and thermal stability of the as‐prepared red phosphors are obviously improved through lattice modification, promoting the corresponding applications in white light‐emitting diodes and optical thermometry.